What Factors Determine the Choices between Joint Venture and Wholly Owned Subsidiary? Experience from China's FMCG Industry - SHAO, ANQI (2011)
This paper aims to use both resource-based theory and institution theory to analyse multinational enterprises’ choices between joint venture and wholly owned subsidiary in the FMCG industry in China, with close investigations into P&G and Coca-Cola. The findings suggest that in addition to transaction cost theory, resource-based theory and institution theory can explain a significant portion of multinational enterprises’ entry mode choice decisions. The results also indicate that compared to other factors, firm size and market orientation are less influential in deciding multinational enterprises’ entry mode choices. In addition, the research also shows that in institution theory, normative institutional variables are weaker than regulative institutional variables and cognitive institutional variables. Furthermore, this paper gives some recommendations to the multinational enterprises in China, Chinese companies, and the Chinese government.